Total soluble and endogenous secretory receptor for advanced glycation end products as predictive biomarkers of coronary heart disease risk in patients with type 2 diabetes: an analysis from the CARDS trial. - Colhoun, H; Betteridge, D; Durrington, P; Hitman, G; Neil, A; Livingstone, S; Charlton-Menys, V; Bao, W; Demicco, D; Preston, G; Deshmukh, H; Tan, K; et al. (2011)
OBJECTIVE: Circulating levels of soluble receptor for advanced glycation end products (sRAGE) likely comprise both a secreted isoform (esRAGE) and wild-type RAGE cleaved from the cell membrane. Both sRAGE and esRAGE have been proposed as biomarkers of cardiovascular disease (CVD), but prospective data are limited. We examined the relationship of sRAGE and esRAGE to incident coronary heart disease (CHD) and stroke in type 2 diabetic patients followed for 3.9 years in a trial of atorvastatin: the Collaborative Atorvastatin Diabetes Study (CARDS). RESEARCH DESIGN AND METHODS: We used a nested case-control design sampling all incident cases of CVD with available plasma and randomly selecting three control subjects, who were free of CVD throughout follow-up, per case. Analysis was by Cox regression with adjustment for treatment allocation and relevant covariates. RESULTS: sRAGE and esRAGE were strongly correlated (ρ = 0.88) and were both higher in those with lower BMI (P < 0.001), higher adiponectin (P < 0.001), lower estimated glomerular filtration rate (P = 0.009), and white ethnicity (P < 0.001). Both sRAGE and esRAGE were associated with incident CHD events, independently of treatment allocation and the above factors; hazard ratio (HR) = 1.74 (95% CI 1.25-2.41; P = 0.002) for a doubling of the sRAGE level; HR = 1.45 (1.11-1.89; P = 0.006) for a doubling of the esRAGE level. There was no significant association with stroke; HR for sRAGE = 0.66 (0.38-1.14). Atorvastatin, 10 mg daily, did not alter sRAGE. CONCLUSIONS: Higher levels of sRAGE and esRAGE are associated with incident CHD but not stroke in type 2 diabetes.